Transformations in Translating Expressions of Women's Objectification from English to Indonesian in a Netflix Series - Evayani, Widya; Sajarwa (JOALL (Journal of Applied Linguistics and Literature), 2024)
Transformations refer to the changes and adaptations occurring when a text is rendered from one language to another. These transformations can involve several aspects of the source text and its rendition into the target text, including how the issue is transferred. One of those issues in the source text is the portrayal of women objectification. Women objectification expression points to the expression that puts women as objects. This study focuses on unloading the form of women’s objectification expression and its transformations in the translation from English into Indonesian. The data source of the research was the transcription of both English and Indonesian subtitles of the Netflix series Anne with an E. Using a qualitative-descriptive approach, the results show that the women are objectified in two ways (1) reduces them into an inert realized by changing pronouns and proper name into names of animals, goods that have no more function, label, and name of dummy object, and judged them by their attributes, such as appearance—body shape, hair; and also behavior—especially on women’s reaction; and (2) Denial of subjectivity by overlooking their agency, thought, and feeling. Moreover, in the translation, women’s objectification expression transforms in the grammatical and lexical stages. At the lexical level, transformation is realized by translating words or phrases using conceptual equations such as the word "trash" becomes "tidak berguna". Although it does not use equivalent words in the dictionary, the equivalence of the sense value from the original text to the source text tends to be achieved. Some expressions are included in zero transformation. Grammatical transformation is realized in the form of substitution, such as English nouns, into Indonesian adjectives and transpositions. The Indonesian translation beholds Indonesian structure and tends to be more subtle in nuance and sense value compared to English.